Driving Omah Yudi’s community empowerment and interest in tourist visits in Temanggung - Nina Mistriani; Dyan Triana Putra; Trenggono Trenggono (The International Journal of Politics and Sociology Research, 2023)
Omah Yudi is a village that has a wealth of natural and cultural tourism potential but still needs development and community empowerment to improve the quality and attractiveness of its tourist destinations. The research method used is a combination of literature studies, field observations, and interviews with related parties. The results showed that to drive Omah Yudi's community empowerment, a standard tourist service strategy is needed which is applied to Omah Yudi homestay, namely homestay as a place to stay, homestay as a place to vacation for tourists, homestay as a living culture, homestay becomes part of a new family, and homestay sells tour packages with the surrounding area, especially the tourist area closest to the tourist attraction. In addition, collaboration between the government, the private sector, and the local community is also as key to creating a sustainable empowerment program. To increase interest in tourist visits, efforts are needed in the strategy of developing the attractiveness of Omah Yudi as an attractive accommodation, improving infrastructure and adequate tourist facilities, as well as more effective and sustainable promotional campaigns. The development of an authentic and memorable tourist experience will also be an important factor in attracting tourists to visit Omah Yudi. This research is expected to provide guidance and recommendations for local governments and tourism industry players in driving community empowerment and increasing interest in tourist visits so that it can have a positive impact on economic development and the welfare of the local community.